2021
DOI: 10.3126/jcmsn.v17i1.33346
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile of Patients Undergoing Colonoscopy at a Tertiary Care Centre in Central Nepal

Abstract: Introduction: Colonoscopy is one of the useful diagnostic tool to evaluate lower gastrointestinal tract. Theaim of this study was to evaluate patient characteristics, common symptoms, colonoscopicfindings and histopathology findings by reviewing colonoscopy procedures. Methods: This was a retrospective study conducted at College of Medical Sciences and teaching hospital, Bharatpur, Nepal over a period of three years (1st January 2017 – 31st December 2019). Census sampling method was used to retrieve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…We found that the mean age of the patients who underwent colonoscopy was 43.8 years, which is comparable to other similar studies done in Nepal 5 7 . However, the median age of patients undergoing colonoscopy was reported to be 62.5 years in a study done in the USA, 57 years in a general hospital in the UK and 59 years in a study done in South Korea 10 12 .…”
Section: Discussionsupporting
confidence: 89%
“…We found that the mean age of the patients who underwent colonoscopy was 43.8 years, which is comparable to other similar studies done in Nepal 5 7 . However, the median age of patients undergoing colonoscopy was reported to be 62.5 years in a study done in the USA, 57 years in a general hospital in the UK and 59 years in a study done in South Korea 10 12 .…”
Section: Discussionsupporting
confidence: 89%